A CLINICAL CASE OF SYNGAP1 GENE MUTATION IN A GIRL WITH EPILEPSY, MENTAL RETARDATION, AUTISM, AND MOTOR DISORDERS - M. Yu. Bobylova; M. B. Mironov; M. O. Abramov; A. V. Kulikov; M. V. Kazakova; L. Yu. Glukhova; E. I. Barletova; K. Yu. Mukhin (Русский журнал детской неврологии)
The introduction of the latest genetic techniques into practice could discover a basis for the comorbidity of genetic epilepsies and behavioral disturbances with cognitive impairments. Some chromosomal syndromes are characterized by a specific electroencephalogram (EEG) pattern, the type of seizures, and the variant of the course of epilepsy. This paper describes a case of synaptic RAS GTP-ase-activating protein 1 (SYNGAP1) gene mutation in a 9-year-old female patient with eyelid myoclonic epilepsy, atypical absences, and atypical autism with mental retardation. The patient’s parents visited a physician for epilepsy (myoclonic absences), markedly delayed psycho-speech development, and specific communication problems in the child. The characteristics of autistic behavior were manifested from birth; routine EEG recorded epileptiform activity at the age of 2 years; epileptic seizures appeared at 5 years. Valproic acid and levetiracetam in this patient exerted a good effect on seizures; however, a clinical and encephalographic remission was achieved by a combination of levetiracetam and ethosuximide. The clinical case including the neurological and psychic statuses, logopedic characteristics, the result of psychological testing, and video-EEG monitoring findings are analyzed in detail.The SYNGAP1 gene is located on chromosome 6p21.3. About 50 cases of SYNGAP1 syndrome are now known worldwide. After normal maternal pregnancy and delivery, the patients show delayed psychomotor development with pronounced regression at 1 to 3 years of age. At this age, there are diffuse polyspike discharges on the EEG or an onset of generalized epileptic seizures (atonic, myoclonic, eyelid myoclonic, and absence seizures), commonly photosensitivity and autoinduction, mental development stops, speech regresses, behavioral disorders that are typical of autism develop. Drug-resistant epilepsy is noted in approximately half of the described cases. There is a correlation between the severity of epilepsy and cognitive deficit.